Degradation of Reactive Dyes Using Advanced Oxidation Method - KÖK YETİMOĞLU, ECE; DENİZ, SABAHATTİN (WILEY, 2015)
In this study, the photo-Fenton process was used to identify degradation conditions of Reactive Blue 19 (RB19) and Reactive Red 21 (RR21). The effects of pH, initial H2O2 and FeSO4 concentrations, time, and UV light intensity in determining the degradation rate were studied. The optimal conditions for the degradation of 0.156 mmol L-1 RB19 and 0.036 mmol L-1 RR21 in water were found to be: pH 4, 0.1 mL 30% H2O2 for RB19 and RR21, 0.2 mL 0.5% FeSO4 for RB19 and 0.1 mL 0.5% FeSO4 for RR21, 20 mL volume, and a temperature of 20 degrees C. Optimal conditions were applied to synthetic dye wastewater using small amounts of H2O2 in 1 L for degradation. The degree of degradation efficiency of synthetic wastewater by the photo-Fenton process was found to be > 95% within 10 min.
Keywords: Photo-Fenton process; Photooxidative methods; RB19; RR21; Textile wastewater; PHOTO-FENTON OXIDATION; TEXTILE WASTE-WATER; EXPERIMENTAL-DESIGN; AZO-DYE; HYDROGEN-PEROXIDE; ELECTRO-FENTON; DECOLORIZATION; EFFLUENTS